Revalidation of Pristimantis brevicrus (Anura, Craugastoridae) with taxonomic comments on a widespread Amazonian direct-developing frog - Ortega-Andrade, H. M.; Ortega-Andrade, H. M.; S. R. Ron,; S. R. Ron, (Herpetological Journal, 2016)
Problems associated with delimi ng species are par cularly pronounced in taxa with high species-level diversity, as occurs in Pris man s frogs. Herein, we resurrect Pris man s brevicrus, nov. comb., from the synonymy of P. altamazonicus, a widespread species in the upper Amazon Basin, based on morphological, acous c and gene c evidence. Both species are sympatric along the Upper Amazon Basin of Ecuador and northern Peru, up to ~1450 m. Phylogene c analyses reveals that P. altamazonicus and P. brevicrus are sister taxa in a well-supported clade with P. diadematus and two uncon rmed candidate species. Pris man s altamazonicus is dis nguished from P. brevicrus by having a di eren ated tympanic annulus, a smooth dorsum with sca ered small tubercles towards the anks, weakly areolate skin on the venter, red to bright orange groin with black mo ling, on hidden surfaces of thighs (bluish-white to yellowish-white in P. brevicrus) of living specimens. The recogni on of P. brevicrus and two uncon rmed candidate species suggest that the diversity of these frogs is inadequately understood, highligh ng the need for more integra ve taxonomic reviews of Amazonian amphibians.
Centro Jambatu - ID 1572